Pengawasan Pemenuhan Hak Hak Pekerja Penyandang Disabilitas di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Nizza Kartika Sari; Wiwik Afifah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
: Â In the midst of limitations, people with disabilities are part of society who have equal rights and opportunities in all aspects of life, including in the world of work. In relation to the rights of workers with disabilities, Article 53 Paragraph (1) of Law No. 8/2016 on persons with disabilities states that â€œThe Government, Regional Governments, State-Owned Enterprises, and Regional-Owned Enterprises are required to employ at least 2% (two percent) of employees or workers with disabilities from the number of employees or non-disabled workers.â€ The constitution has guaranteed the right to work to persons with disabilities, but this has not yet been fully implemented. Although the constitution has guaranteed the right to employment to persons with disabilities, these rights have not been fully realized. The intention of this research is to use empirical research methods, using a legislative approach, conceptual approach and legal sociology approach. Using primary and secondary legal sources used by inventorying and reviewing literature. It can be said that the implementation of the protection of persons with disabilities in Surabaya City is not yet fully in accordance with existing regulations, namely Surabaya Mayor Regulation No. 9 of 2024. This is because there are still many agencies and companies, both public and private, that have not been able to accommodate workers with special needs.Â